Fluorescence induction reveals organization of antenna and reaction center in photosynthetic bacteria - Gerencsér, László; Maróti, Péter (Acta Biologica Szegediensis, 2007)
The photochemical phase of the bacteriochlorophyll fluorescence induction generated by rectangular shape of laser diode illumination was measured in different organization levels {whole cell, chromatophore and isolated reaction center protein) of carotenoidtess mutant of purple photosynthetic bacterium Rhodobacter sphaeroides R-26.1. While the antenna containing species showed large and positive variable fluorescence (fj relative to the constant (initial) fluorescence (Fa) {FJF^ ~ 4.5 in whole ceil), the isolated RC had smaller and negative change (FJF - -0.6). The variable fluorescence of the ceils increased steadily in the function of the age of the cultivated bacterium: FJF0 - 2 for young ceils and FJF0 - 4.5 fór old ceils while the rise time of the fluorescence induction remained constant (- 2 ms). In chromatophore, 7 times higher rate was measured than in isolated reaction center under identical experimental conditions. The results obtained under different conditions are interpreted by an extended version of the Lavergne-Trissl model where the simultaneously measured fluorescence inductions from the antenna and the RC can be separately expressed.